(untitled) (Journal of Engineering, 2012)
This paper describes DC motor speed control based on optimal Linear Quadratic Regulator (LQR) technique. Controller’s objective is to maintain the speed of rotation of the motor shaft with a particular step response.The controller is modeled in MATLAB environment, the simulation results show that the proposed controller gives better performance and less settling time when compared with the traditional PID controller.